Epibenthic community structure in Northeast Greenland and the Kitikmeot Sea in the Canadian Arctic Archipelago - Fredriksen, Rosalyn (UiT Norges arktiske universitet, 2018)
Climate warming in the Arctic results in increased human use of Arctic shelf regions through oil and gas development and increased shipping. Such pressures necessitate the closing of knowledge gaps in poorly studied areas, here two areas located at outflow shelves in the Arctic, to record the current status of epibenthic marine ecosystems. This study characterizes epibenthic community structure, feeding strategies composition and their relation to environmental parameters in Northeast Greenland (NEG) and the Kitikmeot Sea in Nunavut in the Canadian Arctic Archipelago (CAA). Sample collection of trawled epibenthos in NEG was conducted at 33 stations at depths between 65 – 1011 m in August 2015 and September 2017, whereas images of epibenthos in the Kitikmeot Sea were taken at seven stations at depths between 20 – 93 m in August 2016. Abundance estimates were provided from both regions, in addition to biomass estimates from NEG. This study improves the inventory list in these regions with 276 putative species in Northeast Greenland collected by Campelen 1800 shrimp and Agassiz trawls and 33 putative species in the Kitikmeot Sea identified by photographic analysis. All taxa identified were known to occur in other Arctic areas. Arthropoda and Echinodermata were the most taxa rich groups in Northeast Greenland and the Kitikmeot Sea, respectively, while Mollusca and Echinodermata the most abundant taxa and Echinodermata was most biomass rich in NEG. In NEG, four geographically contiguous community clusters were recognized, namely fjord, shelf, shelf break and slope communities. Epibenthic community structure and its variability across the stations in NEG was partly explained by environmental drivers that exhibited gradients from the inner part of Bessel Fjord towards the shelf break and slope, with depth and bottom oxygen concentration as the most important factors, in addition to bottom temperature, salinity and turbidity. In the Kitikmeot Sea, feeding strategies strongly reflected the current situation, with ...